Teacher and peer reports on preschoolers’ sociometric popularity - Peceguina, I. (2020)
This study investigated the association between preschool children’s sociometric popu-larity obtained from peer sociometric nominations and from teachers’ classifications. A total of 1535 children (731 girls and 804 boys), aged between 34 and 89.6 months (M = 61.96, SD = 8.91), and 89 teachers participated in the study. The association between reports from the two sources, although not independent, was weak, with teachers perceiving more children as popular and fewer children as rejected. Teacher and peer classifications were similarly asso-ciated with social skills and behavior problems. Sociometric popularity obtained from teachers, but not from peers, was associated with children’s age and verbal competence. Overall, findings suggest that traditional peer sociometric nominations, even at early ages, are not replaceable by teachers’ classifications of children’s sociometric popularity.